INNOVATION AND CREATIVITY: GROWING A SUSTAINABLE LOCAL ECONOMY - Dita Dismalasari Dewi; Yunita Sopiana; Amândio de Araújo Sarmento; Iyad Abdallah Al- Shreifeen (Adisam Publisher, 2024)
Local economic growth through innovation is often faced with a number of challenges that can hinder its adoption and development. These include infrastructure, access to technology, human resources, financial and policy support, and cultural barriers to change. The research method used in this study is the literature research method. The results show that limited access to resources, technology and specialized skills are the main factors limiting the adoption of innovations at the local level. Inadequate infrastructure such as weak internet connectivity, inefficient transportation networks, and unstable electricity supply were found to be major barriers. In addition, inadequate financial support and government policies that are less supportive of the innovation climate create additional constraints for local businesses. On the human resources aspect, there is a gap in the skills required for innovation, signaling a clear need for capacity building through education and training. While from a cultural aspect, resistance to change was identified as a significant barrier, requiring a more encompassing approach to engage local communities in the innovation process.